A NON-STANDARD METHOD OF SOLVING COMPUTATIONAL GEOMETRY PROBLEMS - BRAICOV, Andrei (Acta et Commentationes, Sciences of Education, 2019)
Computational geometry problems are often encountered in programming contests. In this article we examine some problems that, traditionally, are solved using vectors. Another approach to finding solutions is proposed, less commonly found in the specialized literature.